How do technical and tactical demands of football matches affect the physical performance of elite football referees? Exploring the role of experience - Martinez-Torremocha, G.; Alonso-Callejo, A.; Garcia-Unanue, J.; Gallardo, L.; Sanchez-Sanchez, J.; Felipe, J. L. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to analyze whether the physical demands on elite football referees during matches are influenced by both the physical intensity of the game and the technical-tactical context, to assess the impact of elite experience on the physical demands of referees, and to compare the physical performance of the referees with the performance of the players divided by positions in each match analyzed. Physical demands were recorded on 20 Spanish male football referees during the 2020/21, 2021/22, and 2022/23 seasons over a total of 73 official matches, using Global Positioning Systems for physical demands (total distance [TD], high-speed running [HSR], sprint, and high-intensity acceleration [HI ACC] and deceleration) and WyScout for technical-tactical actions (ball circulation, possession, shot, passes, total turnovers, quick turnovers, and long passes). Referees showed lower values for all variables except in TD (p < 0.05). No significant differences (p > 0.05) were found in referees' physical demands based on experience. Low-experience referees correlated HSR and sprint distances with high-intensity decelerations distances in matches. Medium-experience referees linked HSR, sprinting, and HI ACC distances with greater sprint distances in matches. High-experience referees correlated HSR distance with HSR, sprint, and HI ACC distances match demands. Low-experience referees positively correlated HSR and sprint distances with ball circulation, passes, quick turnovers, and forward passes. In conclusion, referees' experience influenced the adaptation of their physical demands to the technical-tactical and physical factors of competitive matches. This information will help professionals working with referees to develop training programs that better prepare referees for specific challenges.